ANALISIS KINEMATIK MANUVER TERBANG VERTIKAL PADA KOMPONEN SWASH PLATE, ROTOR HEAD DAN ROTOR BLADES HELIKOPTER SEJENIS NBO - 105 MENGGUNAKAN CATIA V5R16 - Sukhairi, Teuku Arriessa; Harahap, Jagodang; Wahju Santoso, Djarot (Akademi Komunitas Negeri Aceh Barat, 2023)
Helicopters have a unique advantage over airplanes in that they can adjust the direction of their blades to generate lift in any direction, allowing them to perform vertical takeoffs and landings and hover in one spot. This capability makes them highly valuable for a variety of operations, including transportation. A crucial component in the helicopter control system is the swash plate, which allows for adjustments to the angle of the rotor blades to achieve specific maneuvers.To manufacture and model components such as the swash plate, rotor head, and rotor blades, CATIA V5R16 software can be used. This involves modeling the individual parts in the workbench part design, assembling them in the workbench assembly design, or conducting kinematic analysis using the DMU Kinematics workbench to obtain values for linear velocity, angular velocity, linear acceleration, and angular acceleration. When compared to manual calculations, the differences between the results produced by the CATIA V5R16 software and theoretical calculations are negligible. Therefore, it can be concluded that CATIA V5R16 software is highly capable and suitable for conducting kinematic analysis of three-dimensional components.